Peran Strategis Agen BRILink dalam Mendorong Ekonomi Lokal: Studi Kasus pada Kecamatan Bawen, Kabupaten Semarang - Hulu, Eben Hejer; Yuliamir, Henry (Mahesa Research Center, 2025)
This study aims to analyze the strategic role of BRILink Agent development in driving local economic growth in Bawen District, Semarang Regency. A descriptive qualitative method was employed, with data collected through in-depth interviews with 10 active BRILink agents, field observations, and a review of supporting documents. The findings reveal that BRILink agents expand access to formal financial services, increase the volume of local economic transactions, and create independent business opportunities that strengthen community economic self-reliance. Agents also serve as promoters of financial literacy, although they face challenges such as limited digital infrastructure, initial capital constraints, and low levels of digital literacy among the community. Theoretically, this study reinforces the concept of community-based financial inclusion. Practically, it offers strategic recommendations, including continuous training for agents, provision of capital assistance or light financing schemes, development of internet network infrastructure, and active involvement of local communities in promoting BRILink benefits. Collaboration among BRI, local governments, the Financial Services Authority (OJK), and MSME actors is essential to build a sustainable financial inclusion ecosystem, broaden banking service access, and comprehensively support village-based economic growth.